Wednesday
March 22, 2017

Post a New Question

Posted by on Friday, March 7, 2008 at 9:40am.

finding the product for (7x+1)(x^2+1) and for the problem (2x+6)(x-10) Also finding the product thank you very much

  • math - , Friday, March 7, 2008 at 10:25am

    It is importnt that you attempt these problems yourself. use the rule that
    (a+b)(c+d) = a(c+d) + b(c+d)
    =ac + ad + bc + bd.

    In other words, add up all the possible pairs of products from each of the two terms in parentheses.

    In the first case, the answer is
    7x^3 + 7x + x^2 + 1

    Now you try the other one.

  • math - , Friday, March 7, 2008 at 10:29am

    Use the rule:

    X(A + B) = X A + X B

    If you take:

    X = (7x+1),

    A = x^2 and

    B = 1,

    you get:

    (7x+1)(x^2 + 1) = (7x+1)x^2 + (7x+1)1 =

    x^2 (7x+1) + 7x+1

    You can now expand the term x^2 (7x+1)

    by using the same rule again. So you put:

    X = x^2,

    A = 7 x,

    B = 1

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question